D-dimers in malignant melanoma: association with prognosis and dynamic variation in disease progress - Desch, Anna; Gebhardt, Christoffer; Utikal, Jochen (International journal of cancer, 2017)
Malignant cells elicit a chronic hemostatic activation in disease progress. This procoagulant activity does not only bear a risk for thromboembolism but also facilitates tumor growth and dissemination. An elevated plasma D-dimer level indicates an activated coagulation and fibrinolysis. In this study, the association of D-dimer levels with clinicopathological parameters and patients outcome in melanoma was investigated analyzing in total 533 melanoma patients retrospectively. Using the cut-off point of 0.6 mg/L D-dimer 145 of the total 533 patients (27.2%) were identified with elevated plasma D-dimer levels. This increased D-dimer level positively correlated with tumor thickness (p = 0.0003), lymph node invasion (p = 0.0004) and metastatic state (p <0.0001). To assess the association of D-dimer levels with progression-free survival (PFS) and overall survival (OS), long-rank test and the Cox proportional hazard model was performed. Univariate analyses revealed that elevated D-dimer levels were significantly associated with decreased PFS (HR:2.89, 95% CI (2.07-7.56), p < 0.0001) and OS (HR:2.22, 95% CI (1.06-4.57), p = 0.035). Moreover, multivariate analyses identified elevated D-dimer levels being associated with poor disease outcome (PFS:HR:2.47, 95% CI (1.23-4.98), p = 0.012; OS:HR:2.01, 95% CI (0.09-4.45), p = 0.087). Additionally, D-dimer levels were significantly increased in terminal stage patients when comparing plasma levels 0-8 versus 24-48 weeks before death (p = 0.0003). In summary, this study presents multiple evidence that elevated D-dimer levels in melanoma patients associate with poor prognosis and therefore plasma levels of D-dimers could reveal a more aggressive phenotype of melanoma and may guide the management of anti-melanoma treatment including the concept of an anti-coagulatory therapy in tumor patients.